Unravelling semi-presidentialism: democracy and government performance in four distinct regime types. Issue 1 (2nd January 2018) - Sedelius, Thomas; Linde, Jonas
ABSTRACT: Do semi-presidential regimes perform worse than other regime types? Semi-presidentialism has become a preferred choice among constitution makers worldwide. The semi-presidential category contains anything but a coherent set of regimes, however. We need to separate between its two subtypes, premier-presidentialism and president-parliamentarism. Following Linz's argument that presidentialism and semi-presidentialism are less conducive to democracy than parliamentarism a number of studies have empirically analysed the functioning and performance of semi-presidentialism. However, these studies have investigated the performance of semi-presidential subtypes in isolation from other constitutional regimes. By using indicators on regime performance and democracy, the aim of this study is to examine the performance of premier-presidential and president-parliamentary regimes in relation to parliamentarism and presidentialism. Premier-presidential regimes show performance records on a par with parliamentarism and on some measures even better. President-parliamentary regimes, on the contrary, perform worse than all other regime types on most of our included measures. The results of this novel study provide a strong call to constitution makers to stay away from president-parliamentarism as well as against the idea of thinking about semi-presidentialism as a single and coherent type of regime.